About the Methodology of Teaching Mathematics - Yanushkevichiene, Olga (European Journal of Social Science Education and Research, 2017)
This paper discusses the teaching of mathematics and developing of logical thinking. Based on the psychology of thinking, the best possible forms of teaching are analyzed. As an example, the compliance with the tasks in one of the mathematical textbooks for elementary school and age peculiarities of children is analyzed.